2017
DOI: 10.1016/j.chemgeo.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of dissolved gases from the Eastern Carpathians - Transylvanian Basin boundary

Abstract: We show the results of a study on the volatiles dissolved in mineral waters discharged over a 200 km-long transect along the Rodna-Bârgău area and Călimani-Gurghiu-Harghita volcanic chain (Eastern Carpathians, Romania terms of mixings among different gas sources feeding the groundwater and the contemporary occurrence of gaswater interactions like degassing and deposition of carbonates, affecting the circulating waters after their infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…The same author, based on isotopic composition, suggested that the Corund North gases have a deep origin possibly due to thermometamorphism of carbonates in the subsurface. The same deep origin was also suggested for the waters in the works of Kis (2013) and Italiano (2017). Our measurements revealed that the maximum free CO2 gas flux is 458.86 g/m 2 /day supporting the CO2 rich environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The same author, based on isotopic composition, suggested that the Corund North gases have a deep origin possibly due to thermometamorphism of carbonates in the subsurface. The same deep origin was also suggested for the waters in the works of Kis (2013) and Italiano (2017). Our measurements revealed that the maximum free CO2 gas flux is 458.86 g/m 2 /day supporting the CO2 rich environment.…”
Section: Discussionsupporting
confidence: 85%
“…The first measurements regarding the composition of the emanated gases in Corund area were performed by Vaselli et al (2002), who demonstrated the dominance of the carbon-dioxide and the presence of methane in the free gas mixture. The same can be concluded about the dissolved gases as well (Italiano et al, 2017).…”
Section: Introductionsupporting
confidence: 57%
“…He isotopic ratios in the fluids collected in this study are up to 3.1 R a similar to those obtained from previous studies (Figure 4 and Table 3). These values are higher than those obtained from the surrounding areas such as in the Carpathian Foredeep and the Transylvanian Basin where He isotopic ratios are between 0.02 and 0.03 R a Italiano et al, 2017;Vaselli et al, 2002, Figure 4). These latter values are typical of crustal fluids dominated by 4 He produced by decay of U and Th (e.g., Ozima & Podosek, 2002).…”
Section: Crustal Assimilation Versus Mantle Metasomatismmentioning
confidence: 66%
“…The minimum total CO 2 flux was estimated to be 8.7 × 10 3 t/year . The aquifers of this area are represented by CO 2 -rich sparkling mineral water, with temperature up to 22.5°C (Berszán et al, 2009;Italiano et al, 2017;Jánosi et al, 2011).…”
Section: Gas Emissions and Mineral Water Springs At Ciomadul Volcanicmentioning
confidence: 99%
“…The heat flow further increases towards the volcanic areas of the Eastern Carpathians, exceeding 120 mW m −2 , in the northern part and at the southern border of the volcanic range. Here there are no documented seeps anymore ( Figure 9) and geothermal, CO 2 -rich manifestations prevail [60]. Some of the uncertain seeps described in the old literature, however, occur within the higher thermal flux zones (Figure 10), as the northern and southern segments of the Eastern Carpathians.…”
Section: Seep Vs Heat Flowmentioning
confidence: 81%